Transcriptional Response of Escherichia coli to External Zinc - Yamamoto, Kaneyoshi (American Society for Microbiology, 2005)
Transcriptional response of Escherichia coli to extracellular zinc was studied using DNA microarray and S1 mapping assays. Addition of external zinc induced the expression of zinc exporter ZntA and inhibited the expression of zinc importer ZnuC. In the continuous presence of zinc, ZnuC repression took place at lower zinc concentrations than ZntA induction. The microarray assay indicated that the addition of excess external zinc induces the expression of many genes that are organized in the regulon for cysteine biosynthesis, implying that cysteine plays a role in transient trapping of free zinc for maintenance of zinc homeostasis. Besides the RpoE regulon, other genes were also induced by zinc, suggesting that periplasmic proteins denatured by zinc induce the genes for protein repair. The microarray data of the newly identified zinc-responsive promoters were confirmed by S1 mapping.